2018
DOI: 10.1021/acsami.7b17274
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effects of Silver Nanoparticles on Lactobacilli and the Underlying Mechanism

Abstract: While the antibacterial properties of silver nanoparticles (AgNPs) have been demonstrated across a spectrum of bacterial pathogens, the effects of AgNPs on the beneficial bacteria are less clear. To address this issue, we compared the antibacterial activity of AgNPs against two beneficial lactobacilli ( Lactobacillus delbrueckii subsp. bulgaricus and Lactobacillus casei) and two common opportunistic pathogens ( Escherichia coli and Staphylococcus aureus). Our results demonstrate that those lactobacilli are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 182 publications
(117 citation statements)
references
References 51 publications
4
110
0
1
Order By: Relevance
“…The leakage of their cytoplasm content from both cells was indicative of the damage of the outer cell walls and inner membrane for both bacteria (red arrow pointed in Figure m and 3p). Thus it can be concluded that the as‐prepared VO x QDs had a direct killing effect on bacteria, which should be attributed to the trace toxic vanadium ions release on the surface of VO x QDs, the overproduction of hydroxyl radical (•OH) and the oxidation of halides X − (such aschloride (Cl − ) orbromide (Br − ) ions) to the corresponding hypohalous acids (HOX) ,. It was reported that VO x nanomaterials possess excellent catalytic performance, such as peroxidase activity, which plays a key role in the bacteriostasis of VO x through the generation of .…”
Section: Methodsmentioning
confidence: 99%
“…The leakage of their cytoplasm content from both cells was indicative of the damage of the outer cell walls and inner membrane for both bacteria (red arrow pointed in Figure m and 3p). Thus it can be concluded that the as‐prepared VO x QDs had a direct killing effect on bacteria, which should be attributed to the trace toxic vanadium ions release on the surface of VO x QDs, the overproduction of hydroxyl radical (•OH) and the oxidation of halides X − (such aschloride (Cl − ) orbromide (Br − ) ions) to the corresponding hypohalous acids (HOX) ,. It was reported that VO x nanomaterials possess excellent catalytic performance, such as peroxidase activity, which plays a key role in the bacteriostasis of VO x through the generation of .…”
Section: Methodsmentioning
confidence: 99%
“…To verify the peroxidase-like property of the Au@PtRu nanorods, we followed the intermediates of the reaction, specically cOH. [36][37][38] The formation of cOH was monitored with terephthalic acid (TA), a typical uorescent probe for the detection of cOH. In the presence of H 2 O 2 , the Au@Pt and Au@PtRu nanorods catalyzed the uorescence of TAOH, indicating the formation of cOH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that nanoparticles affect the bacteria in biofilms via the same mechanisms by which they affect planktonic bacteria. These include physical damage to bacteria from the sharp edges of nanoparticles ( Figure ), ion release, production of reactive oxygen species (ROS) leading to oxidative stress, nanoparticle‐mediated enzyme‐like catalytic activity, and DNA damage ( Figure ). At the same time, many experts have pointed out that the aforementioned mechanisms cannot explain the complex interactions between nanoparticles and biofilms, and any proposed mechanism should take into account the formation and structure of the oral biofilm.…”
Section: Antibiofilm Mechanisms Of Nanoparticles At Different Stages mentioning
confidence: 99%
“…The acidic growth environment (pH as low as 4.5) of L. bulgaricus and L. casei enhances AgNP dissolution and OH production, which results in bacteria death. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Antibiofilm Mechanisms Of Nanoparticles At Different Stages mentioning
confidence: 99%